Adhesion of Endothelial Cells and Endothelial Progenitor Cells on Peptide-Linked Polymers in Shear Flow - Wang, Xin (Mary Ann Liebert, Inc., 2013)
The initial adhesion of human umbilical vein endothelial cells (HUVECs), cord blood endothelial colony-forming cells (ECFCs), and human blood outgrowth endothelial cells (HBOECs) was studied under radial flow conditions. The surface of a variable shear-rate device was either coated with polymer films or covered by synthetic fibers. Spin-coating was applied to produce smooth polymer films, while fibrous scaffolds were generated by electrospinning. The polymer was composed of hexyl methacrylate, methyl methacrylate, poly(ethylene glycol) methacrylate (PEGMA), and CGRGDS peptide. The peptide was incorporated into the polymer system by coupling to an acrylate-PEG-N-hydroxysuccinimide comonomer. A shear-rate-dependent increase of the attached cells with time was observed with all cell types. The adhesion of ECs increased on RGD-linked polymer surfaces compared to polymers without adhesive peptides. The number of attached ECFCs and HBOECs are significantly higher than that of HUVECs within the entire shear-rate range and surfaces examined, especially on RGD-linked polymers at low shear rates. Their superior adhesion ability of endothelial progenitor cells under flow conditions suggests they are a promising source for in vivo seeding of vascular grafts and shows the potential to be used for self-endothelialized implants.